Undernutrition and associated factors among pregnant women in Ethiopia. A systematic review and meta-analysis - Zewude, Shimeles Biru; Beshah, Mekonen Haile; Ahunie, Mengesha Assefa; Arega, Dawit Tiruneh; Addisu, Dagne (Frontiers in Nutrition, 2024)
Maternal undernutrition, is a major public health concern due to its association with mortality, and overall disease burden for mothers and their children. Maternal nutrition determine pregnancy outcome since reduced intake of nutrients influence gestational age length, placental function and fetal growth during pregnancy. The complexity of the intergenerational aspects of maternal nutrition may also confound the design of interventions. Therefore, this research aimed to assess the prevalence of undernutrition and associated factors among pregnant woman in Ethiopia.We identified literature from PubMed, EMBASE, Scopus, and CINAHL databases. Data were entered into Microsoft excel and then exported to Stata version 17 statistical software for analysis. The I 2 and Q-statistic values detect the level of heterogeneity and meta regression were performed to investigates between-study heterogeneity using more than one moderators. JBI quality assessment tools were used to include relevant article. Evidence of publication bias was indicated using Funnel plot and Egger's linear regression test. The effect size was expressed in the form of point estimate and odds ratio 95% CI in the fixed effect model.Nineteen studies fulfill the inclusion criteria. The pooled prevalence of undernutrition among pregnant women was 32% (95% CI 31.3-33.2 I 2 =97.5%, P<0.0). Illiteracy (AOR= 3.6 95%CI;), rural residence (AOR=2.6 95% CI; 1.2-3.5), lack of prenatal dietary advices (AOR=2.6 95% CI; 1.8-3.7), household food insecurity (AOR=2.5 95%CI; 1.9-3.2), Low dietary diversity score (AOR=3.7%CI; 2.2-5.9) appears to be significantly associated with undernutrition among pregnant women.The review showed that the prevalence of undernutrition still high among pregnant women.Illiteracy, rural residence, lack of prenatal dietary advices, household food insecurity, and low dietary diversity score were significantly associated with undernutrition during pregnancy.Interventions should concentrate on educating the public and helping family access the food or supplements they need through local markets, health systems, and community-based support, as undernutrition is caused by numerous interconnected causes.